"I Will Bless Those Who Bless You": Evangelicalism and Support for Israel in Latin America. Issue 3 (September 2022) - Ziv, Tom
Abstract: The relations of the Evangelical movement and Israel have drawn the attention of many scholars of religion, public opinion, and political science in the last two decades. This study examines the influence of Evangelicals on their country's policy toward Israel. I conduct the first quantitative, cross-national research, investigating the links between the size of the Evangelical population of a country and its support for Israel. Analyzing 198 UN General Assembly votes of 18 Latin American countries from 2009 to 2019, my results show that as the Evangelical population in a country grows, so does its support for Israel. Unpredictably, I also find that a state of armed conflict between Israel and the Palestinians does not decrease the support for Israel.